Strangulated small bowel obstruction caused by isolated obturator nerve and pelvic vessels after pelvic lymphadenectomy in gynecologic surgery: two case reports - Riko Ideyama; Yoshihisa Okuchi; Kenji Kawada; Yoshiro Itatani; Rei Mizuno; Koya Hida; Kazutaka Obama (Surgical Case Reports)
Abstract Background Although small bowel obstruction (SBO) is a major complication occurring after abdominal surgery, few reports have described strangulated SBO after pelvic lymphadenectomy (PL). This report describes two cases of strangulated SBO caused by a skeletonized obturator nerve and pelvic vessels after laparoscopic PL during gynecologic surgery. Case presentation Case 1: A 57-year-old woman with endometrial cancer underwent a laparoscopic semi-radical total hysterectomy with PL. Nine months after the operation, she visited our emergency room complaining about subacute pain spreading in the right groin, right buttock, and dorsal part of the right thigh. She had no abdominal pain. Although her symptoms were not typical, computed tomography (CT) revealed strangulated SBO in the right pelvis. Laparoscopic surgery revealed that the small bowel was ischemic. Then we converted to open surgery. We transected the right obturator nerve and umbilical artery, which constructed an internal hernia orifice in the right pelvis, followed by resection of the ischemic small bowel. Fortunately, during 6-month follow-up, she showed only slight difficulty in walking as a postoperative complication. Case 2: A 62-year-old woman with cervical cancer underwent laparoscopic radical hysterectomy with PL. Six months after the operation, she visited our hospital emergently because of sudden onset of abdominal pain and vomiting. CT showed strangulated SBO. Urgent laparoscopic surgery exhibited the incarcerated small bowel at the right pelvis. Consequently, we converted to open surgery. The terminal ileum was detained into the space constructed by the right umbilical artery. We cut the umbilical artery and performed ileocecal resection. After the surgery, she was discharged with no complication or sequela. Conclusion When examining a patient after PL who complains of severe pain or symptoms, one should consider the possibility of PL-related SBO, even if the pain is apparently atypical for SBO.